Pengaruh Optimisme Terhadap Kesejahteraan Subjektif Pada Remaja Yatim Piatu di Kota Makassar - Ahyar, Muhammad Abizar Nafara Aliyandra; Tetteng, Basti (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Orphaned adolescents are individuals who are in the adolescent development phase and have lost one or both parents due to death. The sudden severance of the emotional bond between parents and children is caused by death on a person's subjective well-being. Optimism is one of the things that can affect subjective well-being in adolescents. This study aims to see whether there is an influence of optimism on subjective well-being in orphaned adolescents in Makassar City. Respondents in this study amounted to 313 people with the criteria of Orphaned Adolescents Aged 17-21 Years in Makassar City. The measuring instruments used in this study were the subjective well-being and optimism scales. The data in this study were analyzed using a simple regression analysis test. The results of the data analysis showed a significance value of 0.000, meaning that there is an influence of optimism on subjective well-being in orphaned adolescents in Makassar City. The r value obtained was 0.74, indicating that optimism has a positive relationship with the subjective well-being of orphaned adolescents in Makassar City. The implications of this study are that it can contribute to the development of science related to optimism and subjective well-being in orphaned adolescents, and can be used as a guideline for students and future researchers.